Uma Nova Theraphosea (Avicularidae) Brasileira, ð˜—ð˜¢ð˜®ð˜±ð˜©ð˜°ð˜£ð˜¦ð˜µð˜¦ð˜¶ð˜´ ð˜±ð˜ªð˜³ð˜¢ð˜¤ð˜ªð˜¤ð˜¢ð˜£ð˜¦ð˜¯ð˜´ð˜ªð˜´ s. n. - Piza Junior, Salvador de Toledo (REVISTA DE AGRICULTURA, 2019)
Uma Nova Theraphosea (Avicularidae) Brasileira,Â ð˜—ð˜¢ð˜®ð˜±ð˜©ð˜°ð˜£ð˜¦ð˜µð˜¦ð˜¶ð˜´ ð˜±ð˜ªð˜³ð˜¢ð˜¤ð˜ªð˜¤ð˜¢ð˜£ð˜¦ð˜¯ð˜´ð˜ªð˜´ s. n.